Mastitis vaccination using a commercial polyvalent vaccine or a herd-specific Staphylococcus aureus vaccine - Freick, Markus; Frank, Yvonne; Steinert, Kathrin; Hamedy, Ahmad; Passarge, Oliver; Sobiraj, Axel (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2016)
Objective of this study was the improvement of selected parameters of udder health by mastitis vaccination in a dairy herd with elevated bulk milk somatic cell counts and Staphylococcus (S.) aureus as predominant mastitis causing pathogen. Material and methods: On a dairy farm, pregnant heifers (status group [SG] 1; n = 181) as well as cows stratified for their udder health state (classification based on results of cytobacteriological investigations of quarter milk samples obtained before dry cow therapy [MS0]) (SG 2–4; n = 416) were randomly assigned to one of the following vaccination groups (VG): Startvac® (VG SV), Bestvac® Rind Mastitis (containing herd-specific S. aureus-strains; VG BV) and the unvaccinated control (VG Co, placebo), respectively. The collected data (5 [MS5] and 52 [MS52] days in milk [DIM]: quarter milk somatic cell count [QSCC] and bacteriological investigation of quarter milk samples; dairy herd improvement test [DHIT] days 1–10: milk yield and individual cow somatic cell count; until 305 DIM: clinical mastitis cases) were compared between the VG within their SG. Results: S. aureus prevalences were significantly lower in VG SV (p < 0.001) and VG BV (p = 0.006) within SG 3 and in VG SV (p = 0.008) within SG 4, respectively, in comparison to VG Co. Milk yields (DHIT days [p = 0.042] and 305-day milk yield [p = 0.040]) were significantly less in VG SV within SG 4 compared to VG Co. Significant different changes over time in comparison to VG Co indicating a vaccine effect during lactation were only observed for QSCC within SG 4 for VG BV (p = 0.017; increase towards MS52) and for S. aureus prevalence within SG 3 for VG BV (p < 0.001; opposing trends from MS0 towards MS52). All other interactions of time and VG under investigation were not significant in any of the SG. Furthermore, there were no descriptive differences in the incidence of clinical mastitis and duration of a necessary mastitis therapy, respectively, between the VG within their SG. Conclusion: In this field study, the application of two different mastitis vaccines was not an appropriate tool to improve the considered parameters of udder health sustainably.
Keywords: Dairy cows; udder health; prophylaxis; somatic cell count